Antisemitism in Galicia agitation, politics, and violence against Jews in the late Habsburg monarchy - Buchen, Tim 1979- (Berghahn, 2020)
"In the last third of the nineteenth century, the discourse on the "Jewish question" in the Habsburg crownlands of Galicia changed fundamentally, as clerical and populist politicians emerged to denounce the Jewish assimilation and citizenship. This pioneering study investigates the interaction of agitation, violence, and politics against Jews on the periphery of the Danube monarchy. In its comprehensive analysis of the functions and limitations of propaganda, rumors, and mass media, it shows just how significant antisemitism was to the politics of coexistence among Christians and Jews on the eve of the Great War"--
Includes bibliographical references and index
Keywords: Geschichte 1900; Antisemitismus; Galizien; Antisemitism / Austria / History / 19th century; Antisemitism / Galicia (Poland and Ukraine) / History; Jews / Austria / History / 19th century; Galicia (Poland and Ukraine) / Politics and government / 19th century; Hochschulschrift